Penerapan Variasi Metode Pembelajaran Pada Pelaksanaan Pembelajaran Aksara Dasar Pegon: Studi Kasus pada Peserta Didik Kelas IV di SDI Terpadu Al Badr Ploso Kediri - M. Asep Fathur Rozi; Ahmad Sunoko; Elis Eliana (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2021)
The purpose of this research is to find out and understand the application of various learning methods that are implemented to the success of students in the basic learning process of the Pegon script at the fourth grade elementary school level at SDI Terpadu Al Badr Ploso. The method used in this study is the Field Research method and uses a qualitative approach, because this research will emphasize more on collecting qualitative data and using data analysis in making conclusions. The results of this study indicate that (1) the application of learning methods in the implementation of Pegon learning, students look conducive and enthusiastic in participating in learning, their enthusiasm becomes motivated by the convenience of using the method. (2) The method used at SDI Terpadu Al Badr Ploso is the lecture method, quiz, reward, stupid, question and answer, teacher observation, approach to students, demonstration method, cooperative, drill method. (3) Students are said to be successful if students are able to write without seeing examples, memorize Tarqib (an abbreviation in Pegon learning), understand the meaning of the books, and are able to apply what is obtained in Pegon learning. The purpose of using various methods is so that students do not get bored quickly in learning. In addition, so that the learning conditions of students are comfortable and fun. The importance of learning the Pegon script from an early age is to hope that there will be future generations of the ancestors to make a tradition of learning the meaning of the books. Because in the book there are extraordinary life lessons, from life in the mother's belly to life in another realm